Efficacy and Safety of Pulsed Magnetic Therapy in Sleep related Disorders: A Remote, Randomized, Double-Blind, Placebo-Controlled Trial - Marmann, Peter; Schmieke, Marcus (Journal of Sleep And Sleep Disorder Research, 2026)
Background/Aim Sleep disturbances are common and are associated with impaired daytime functioning, reduced quality of life, and increased health risks. Non-pharmacological neuromodulatory interventions have gained interest as alternatives to hypnotic medication. Pulsed electromagnetic field (PEMF) therapy has been proposed as a non-invasive approach to improve sleep quality and recovery, but evidence from large, well-controlled trials remains limited. The objective of this study was to evaluate the efficacy and safety of pulsed magnetic field therapy (PMT) on sleep quality, sleep-related symptoms, daytime functioning, and well-being in adults with heterogeneous sleep complaints.  Materials and Methods In this remote, randomized, double-blind, placebo-controlled trial, 217 adults reporting non-restorative sleep, difficulties initiating sleep, or frequent nocturnal awakenings were assigned to active PMT using a PEMF device (Night Harmony Female/Male protocol) or a sham application for three weeks. Primary outcomes were changes in the Pittsburgh Sleep Quality Index (PSQI) global score and self-rated sleep satisfaction, restfulness, and sleep initiation difficulties. Secondary outcomes included sleep diary measures, daytime functioning, well-being (WHO-5), symptom burden (MYMOP), and daytime sleepiness (Epworth Sleepiness Scale). Analyses followed the intention-to-treat principle using ANCOVA with baseline values of the respective parameter as covariate.  Results Both groups showed significant improvements over time in global sleep quality and most secondary outcomes (p < 0.001). Between-group differences in PSQI global score were not significant (p = 0.314). However, active PMT resulted in significantly greater improvements in subjective sleep satisfaction (p = 0.02) and restfulness (p = 0.02), particularly among participants with moderate to severe baseline sleep disturbances (p < 0.001 for both). Sleep continuity measures improved similarly in both groups. No serious adverse events were reported.  Conclusions PMT produced modest but significant improvements in subjective restorative aspects of sleep beyond placebo effects and was well tolerated. Further studies using objective sleep measures and longer follow-up are warranted.
Keywords: Pulsed Magnetic Therapy; PEMF; Sleep Quality; Placebo-Controlled Trial; Neuromodulatory